PENGARUH GAYA KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT BINTANG REZEKI MAJU MEDAN - Audina, Bella Nelfa; Yosephine Simanjuntak, Demak Claudia; Buulolo, Desrahmat; Lumban Tobing, Diego Andreas; Sanjaya, Putra (EDUTECH CONSULTANT, 2019)
This study aims to examine and analyze the influence of leadership style and communication on work performance in PT Bintang Rezeki Maju Medan. The existence of a phenomenon of leaders who are less open to innovative ideas and less active in welcoming opportunities, communication processes that take place in the form of one direction, and a decrease in employee performance can be seen from not achieving sales targets behind this research. The sampling technique used is simple random sampling with a total sample of 110 employees. The method used is a quantitative approach with a type of quantitative descriptive research and the nature of research is descriptive explanatory. The data analysis method used is multiple linear regression. The results of the research with a significant level of 0.05 indicate that partially the leadership style has a positive and significant effect on work performance where Tcount 3.036> Ttable 1.98238, and communication has a positive and significant effect on work performance where Tcount8,072 > Ttabel 1,98238. In addition leadership and communication styles have a positive and significant effect on work performance simultaneously, with the results of Fcount 45.570> Ftable 3.08.